2020
DOI: 10.21203/rs.2.16649/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic profiling revealed key signaling pathways for cold tolerance and acclimation of two carp species

Abstract: Background Closely related species of the carp family ( Cyprinidae ) have evolved distinctive abilities to survive under cold stress, but molecular mechanisms underlying the generation of cold resistance remain largely unknow. In this study, we compared transcriptomic profiles of two carp species to identify key factors and pathways for cold tolerance and acclimation. Results Larvae of Songpu mirror carp and Barbless carp that were pretreated at 18°C for 24 hours significantly improved their survival rates und… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
2
1
Order By: Relevance
“…However, the JNK was not activated by cold stress and had no functions in regulating cold resistance of zebrafish larvae. This is inconsistent with previous study in common carp ( Cyprinus carpio L.) [ 27 ]. This may be ascribed to the genetic differences between these two species.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the JNK was not activated by cold stress and had no functions in regulating cold resistance of zebrafish larvae. This is inconsistent with previous study in common carp ( Cyprinus carpio L.) [ 27 ]. This may be ascribed to the genetic differences between these two species.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies identified numerous cold responsive genes (CRGs) from fish including both research models and farmed species. Genes such as the cold-inducible RNA binding protein ( cirbp ), high mobility group box ( hmgb ) and stearoyl-CoA desaturase ( scd ) were revealed to be the marker genes induced by cold stress [ 17 , 18 , 21 , 27 ]. Many CRGs demonstrate no changes in overall abundance but undergo alternative splicing upon cold stress [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation